(untitled) (Brazilian Journal of Oceanography, 2007)
Wave action in sandy beach surf zones and its influence on species composition were evaluated at three sites at Pontal do Paraná, Paraná State, between June/2004 and May/2005. At each sampling site, five hauls were performed monthly using a 15 m long, 2.6 m height beach seine with a 5 mm mesh-size. Samplings were carried out at low water spring tides during daylight. A total of 26,866 fishes were collected, amounting to a total weight of 84,838 kg, which were distributed amongst 28 families and 63 taxa. Multi- and univariated methods used indicated that sheltered and moderately exposed beach samples had similar ichthyofaunal composition, being clupeids and engraulids the most abundant at these beaches. Although abiotic factors differed significantly between beaches, depth appears to exert the major influence on ichthyofauna structure by providing less turbulent waters which might have permitted shoals maintenance. Conversely, exposed beach samples differed largely from the other beaches and were influenced primarily by wave height and salinity variables. These were displayed at CCA diagram and through the occurrence of P. virginicus, M. littoralis and T. goodei.